Antimicrobial susceptibility, biofilm formation, and virulence genes among atypical enteropathogenic Escherichia coli stool isolates in Tehran, Iran - Shahnaz Halimi; Akram Rezaei; Shirin Mohebi; Farhad Bonakdar Hashemi (Iranian Journal of Microbiology)
Background and Objectives: Enteropathogenic Escherichia coli (EPEC) strains are emerging pathogens around the world, particularly among pediatric patients in developing countries, such as Iran. This study aims to examine and compare the characteristics of EPEC isolates from patients, who suffer from diarrhea versus isolates from patients without diarrhea. Materials and Methods: A total of 734 stool specimens [440 diarrheal (D), and 294 non-diarrheal (ND)] were examined. Thirty-six EPEC isolates (26 D, and 10 ND) were recovered by culture on MacConkey agar, followed by biochemical tests. Using PCR assay, eae+; stx1- and stx2-gene profiles of EPEC isolates were confirmed. The antimicrobial resistance was assessed by disk diffusion assay. Biofilm formation was assessed using a standard semi-quantitative microtiter plate assay. Virulence-associated genes, ehac, espA, fimA, flu, and sslE were detected. Results: E. coli comprised 14% of all isolates were EPEC isolates that showed the highest sensitivity to imipenem (IPM) (100%) and gentamicin (GEN) (89%). However, susceptibility to ciprofloxacin and cotrimoxazole or trimethoprim\sulfamethoxazole (SXT) was only 28% and 39%, respectively. About 61% of isolates produced Moderate Biofilm (MB), and the frequency of Weak Biofilm (WB) formers (27%) was higher among D and ND isolates, which carried virulence genes more frequently than D isolates. Conclusion: Preventive measures by public health authorities can thwart the imminent crisis of widespread zoonotic contamination of the food chain in Iran. Our results may help clinicians make optimal therapeutic choices during the treatment of patients with severe EPEC infections, and assist epidemiologists devise policies for effective control of outbreaks.